ESRA19-0168 Ultrasound guided supra-inguinal femoral nerve block for total hip arthroplasty. (30th August 2019) - Sebastian, MP; Sell, A; Shanmuganathan, S; Mihaylov, D; Mcgrath, J
Abstract : Background and aims: Total hip arthroplasty (THA) leads to severe postoperative pain. Femoral nerve block (FNB) or fascia iliaca block performed at the level of inguinal crease failed to show benefit after THA as innervation of the anterior capsule is mainly supplied by proximal FN branches. We analyse the contribution of ultrasound guided (USG) supra-inguinal FNB (SIFNB) to postoperative pain. Methods: After local institutional approval, a retrospective case study was conducted including patients aged >18 years who underwent THA and had USG SIFNB. Primary outcome was numerical pain rating scale scores (NPSS). Secondary outcomes included ease in identifying SIFN, mobility within 24h and opioid consumption. SIFNB Technique: With the patient in supine position and hip extended, a linear transducer is placed tranversally at the level of the ASIS to identify the iliacus muscle in the iliac fossa. the probe is moved medial and caudal to find the FN emerging from the lateral border of the psoas major muscle. the needle is introduced using an in-plane technique from lateral to medial. 10–20 ml of 0, 25–0, 35% levobupicaine were used. Results: 12 patients were included; 8 had general anaesthesia and 4 had spinal anaesthesia. Median NPSS (range) were 0 (0–10) in recovery, and at rest and movement were 0 (0–8) on ward arrival, 1 (1–3) and 2 (0–5) at 12h, 0 (0–5) and 1.5 (0–5) at 24h, and 0 (0–4) and 0 (0–6) at 48h. SIFN was identified in all patients and all were able to mobilize within 24h. Conclusions: We describe a novel technique to approach the FN. SIFNB as part of multimodal analgesia provides good postoperative management and early mobilization in our patients.